PEMETAAN MODEL PEMBELAJARAN YANG TEPAT SEBAGAI PENUNJANG PEMBELAJARAN DI JAKARTA TIMUR - Julinda Siregar; Muhammad Noor.; Ari Whindayati; Yusmaini, Siti Fatimah; Siti Fatimah; Dwi Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to map the appropriate learning models as a support for effective learning processes in secondary schools. A qualitative approach was employed with purposive sampling, involving teachers, the principal, curriculum coordinators, and students, to obtain data from the perspectives of implementers, managers, and recipients of learning. Data collection techniques included semi-structured in-depth interviews and participatory observations, while data analysis was conducted using thematic analysis encompassing transcription, coding, categorization, and triangulation to ensure credibility. The results indicate that the selection and suitability of learning models, such as group discussions, project-based learning, and Problem-Based Learning (PBL), significantly influence learning effectiveness, as they are tailored to student characteristics, learning materials, and curriculum objectives. The appropriate application of these models enhances motivation, active participation, creativity, critical thinking skills, and academic achievement. Key challenges in implementation include student ability differences, time constraints, and media readiness, which can be addressed through school support, including teacher training, facilities, and gradual guidance. Collaboration among teachers, curriculum coordinators, and the principal is crucial for optimizing learning models and comprehensively developing student potential. This study provides implications for developing effective and innovative learning practices.